Spending Behaviour Toward the Financial Aid During COVID-19 in Sarawak - Abdul Hayy Haziq, Mohamad; Rossazana, Ab Rahim; MUHAMAD RIAS K, V ZAINUDDIN; Abdul Rahman Educe, Kushairi (Human Resource Management Academic Research Society, 2024)
Coronavirus (COVID-19) is highly contagious infection that has become a global public health issue. In order to prevent the spread of the COVID-19 pandemic in Malaysia on March 18, 2020, the government issued a Movement Control Order (MCO) restricting travel into and out of the nation including Sarawak. The MCO has slowdown the economy and many people were losing their income. The financial aid in the form of cash transfer is a fiscal policy to enhance the economy flow during the MCO. This study is focusing the behaviors of people in Sarawak on their spending behaviour after received the cash transfers from the government. This study is using the non-parametric methods to analyses the spending behaviour involving 186 respondents in Sarawak. This study also examinate the regression of saving, paying debt, buying grocery and investment toward the spending behaviour to identify the successful of cash transfer policy. The findings indicate that in order for the spending behaviour towards the financial assistance programme to be successful, the citizen needs to spend their money on things like paying debt and buying groceries.